MECHANICAL PROPERTIES OF A DEVELOPED FOAMED CONCRETE - MOHAMMAD, F; SHAWNIM, P (Journal of Duhok University, 2017)
This paper investigates the mechanical properties at a fresh and hardened states of a new foamed concrete. The aim is to develop and produce a hydrophobic lightweight foamed concrete with enhanced properties for structural use. Foamed concrete generally is made of ordinary Portland cement (OPC), fine aggregates, foaming agent, admixtures and water. Metakaolin (MK) and water reducing admixture were used with the mix in this study. The physical properties of the mixes in their fresh state, mainly the consistency of the mixes was determined. All the mixes prepared were undergone rheology test at fixed water/cement (w/c) ratio of 50%, testing for flowability and spreadability. Compressive strength testing was carried out on 100 mm cubes and the results revealed that the compressive strength of foamed concrete decreases with a reduction in density. Flexural strength and flexural modulus, which were tested on 100 x 100 x 500 mm prisms, were also found to decrease with the reduction in density. The use of MK improved compressive strength as well as flexural strength development for normal and foamed concrete. Higher improvement was noted for the flexural strength with the use of a higher dosage of MK.